Development of a patient-reported outcome measure (PROM) screening strategy for early palliative care needs in outpatients with advanced cancer. Issue 28 (1st October 2022) - Kaufmann, Tara L.; Rocque, Gabrielle Betty; Kvale, Elizabeth Ann; Kamal, Arif; Pignone, Michael; Bennett, Antonia Vickery; Saxton, John; Hernandez, Rabecca-Kimberly; Stover, Angela M.
Abstract : 203 Background: There is a critical need to develop standardized and feasible methods to monitor patients for unmet palliative needs and direct timely referral to specialty palliative care. We developed a patient reported outcome measure (PROM) measurement strategy to screen patients for multidimensional palliative care needs. Methods: Guided by evidence-based frameworks for early palliative care in oncology, we identified 8 key domains for PROM monitoring that are meaningful and actionable in clinical care and appropriate for direct patient report. We conducted a systematic search for PROMs assessing these key domains using the Palliative Care Research Cooperative (PCRC) Measurement Core resources and the Grid-Enabled Measures Database. PROMs for each domain were compared for content coverage, psychometric properties, proprietary availability, Spanish translation, and attributes (response options, length, literacy demand). Results: We selected 13 PRO items for weekly monitoring (Symptom PROs) and 11 PRO items for monthly monitoring (Palliative PROs) (Table). We did not identify any validated PROMs to assess caregiver burden from the patient perspective. Validated PROMs in short formats for spiritual/existential needs are limited. Conclusions: Existing PROMs are limited in capturing the multi-dimensionality of palliative care needs for patients with cancer, particularly for spiritual needs and patient-reported caregiver burden. Future work will focus on piloting identified PROMs to monitor patients for early palliative care needs and determining thresholds to trigger referrals to specialty palliative care.Early Palliative Care Domains PRO Measure 1 Number of Items Physical PRO-CTCAE 11 Psychological PRO-CTCAE: Depression/Anxiety 2 Spiritual/Existential FACIT-SP-12 (1, 4, 8, 12) 4 Distress/Coping PRO-CTCAE Psychological PCC-CA-36: Managing Uncertainty Subscale No Additional Social Support PRAPARE: Social Support 1 Caregiver Burden QDACT-PC 1 Patient-Centered Care Patient request for referral 1 Communication & Shared Decision-making PCC-CA-36: Managing Uncertainty Subscale 4 1 PRO-CTCAE: Common Terminology Criteria for Adverse Events; FACIT-SP-12: Functional Assessment of Chronic Illness Therapy – Spiritual Well-Being; PRAPARE: Protocol for Responding to and Assessing Patients' Assets, Risks, and Experiences; QDACT-PC: Quality Data Collection Tool for Palliative Care; PCC-CA-36: Patient-Centered Communication in Cancer Care.